2013
DOI: 10.1039/c3ta10360a
|View full text |Cite
|
Sign up to set email alerts
|

Solar hydrogen evolution using metal-free photocatalytic polymeric carbon nitride/CuInS2 composites as photocathodes

Abstract: a Polymeric carbon nitride (g-C 3 N 4 ) films were synthesized on polycrystalline semiconductor CuInS 2 chalcopyrite thin film electrodes by thermal polycondensation and were investigated as photocathodes for the hydrogen evolution reaction (HER) under photoelectrochemical conditions. The composite photocathode materials were compared to g-C 3 N 4 powders and were characterized with grazing incidence X-ray diffraction and X-ray photoemission spectroscopy as well as Fourier transform infrared and Raman spectros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
92
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(98 citation statements)
references
References 49 publications
5
92
0
Order By: Relevance
“…14, 15 Huda and Turner also concluded that light-induced electron-hole pairs may remain conned within the heptazine subunits 16 which could be later, to some extent, substantiated by analysis of time-resolved photoluminescence spectra. 17 Modication of the g-C 3 N 4 bulk geometry toward the nano-scale is therefore required to remedy these limitations.…”
Section: -10mentioning
confidence: 99%
See 3 more Smart Citations
“…14, 15 Huda and Turner also concluded that light-induced electron-hole pairs may remain conned within the heptazine subunits 16 which could be later, to some extent, substantiated by analysis of time-resolved photoluminescence spectra. 17 Modication of the g-C 3 N 4 bulk geometry toward the nano-scale is therefore required to remedy these limitations.…”
Section: -10mentioning
confidence: 99%
“…To overcome this limitation, the fabrication of macroscopic solid state (photo-) electrodes with compact g-C 3 N 4 lms was soon suggested. 14,15 In this latter approach, overall water splitting is realized under sustained operation in a photoelectrochemical cell, coupling an oxygen evolving anode via external circuitry to the carbon nitride cathode. Electrons consumed at the g-C 3 N 4 electrode are thereby relled by the counter reaction at the anode according to:…”
Section: -10mentioning
confidence: 99%
See 2 more Smart Citations
“…The photocurrent of g-C 3 N 4 /CuInS 2 composite electrode was stable for 22 h in 0.1 M H 2 SO 4 aqueous solution. It was considered that the network of nanoporous g-C 3 N 4 crystallites could strongly protect the CuInS 2 substrate from degradation and photocorrosion under acidic conditions [79].…”
Section: Surface Modificationmentioning
confidence: 99%